Cushing's syndrome induced by misuse of topical corticosteroids in a child with psoriasis vulgaris (Medical Journal of Indonesia, 2008)
Prolonged exc)genous corticosteroid aclministration may cause Cushingi syndrome. However the development of Cushing's syndrome from topical corlico,sleroid therapy is rare. A 7½-year-old boy has suffered from psoriasis vulgaris since the age of nvo. He was treated by a dermatologist with a mixlure of 3% salicylic acid, 50% liquor carbonis delergens, 10 grams of 0.1% mometasonefuroate ointment, ancl 5 grams combination cream consisting of 0.1% gentamycin sulphate and 0.0250 Ãfiuocinolone acetonide. The parents continued the treatment without the doctorb supervision. They applied it lo all over the patient's body three times dailyfor 3½ years. The patient showed milcl hypertension, moonface, btffilo hump, obesity, multiple striae, and suppression of hypothalamus-pituitary-adrenal axis. The bone minerttl density and bone age examinations revealed normal results. Children are more prone to develop systemic side fficts of topical medicalion beccntse o/'their higher ratio of btal body surface area to body weight. Corticosteroid must be used with great care, especially in children. It is very important to inform the parents abott polential side effects of corticosteroid. (Med J Indones 2008; 17: 281-6)